Child malnutrition in Nigeria: Evidence from Kwara State - Kuku-Shittu, Oluyemisi; Onabanjo, Oluseye; Fadare, Olusegun; Oyeyemi, Motunrayo (International Food Policy Research Institute, 2016)
Poverty and a lack of awareness seem to be at the heart of the problem of childhood malnutrition in Nigeria. Until the socioeconomic status of the vast majority of Nigerians improves significantly, malnutrition will continue to pose a serious threat to the growth and development of Nigerian children and the future of national development. Significant variations exist in the level of child and maternal malnutrition across rural/urban settings, geopolitical zones, and agro-ecological bands in Nigeria. Malnutrition rates are higher among rural households who depend more on agriculture than on other sectors for their livelihoods. A range of socioeconomic, demographic, and public health related factors work together to influence maternal and child nutrition outcomes among rural and urban dwellers across the geopolitical zones and agro-ecological zones in Nigeria.